Malaysia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This report discusses Malaysia's economic accomplishment and other economic reforms. Malaysia has attained a strong growth in 2012, and a robust growth is expected in the next term. The financial position of Malaysia is sound and supported by a strong regulatory framework with high bank capitals, international reserves, and refined monetary and financial policies. Fiscal policies need to be restructured, and public financial management needs to be strengthened to deal with risks. The authorities expected Malaysia to be a high-income nation by 2020.